2019
DOI: 10.1029/2018rs006757
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Radar Data Sampling on the Accuracy of Atmospheric Refractivity Inversions Over Marine Surfaces

Abstract: The turbulent nature of the marine atmospheric boundary layer and interactions across the air‐sea interface cause ever‐changing environmental conditions, including atmospheric properties that affect the index of refraction, or atmospheric refractivity. Variations in atmospheric refractivity lead to many types of anomalous propagation phenomena of electromagnetic (EM) signals; thus, improving performance of EM systems requires in situ knowledge of the refractivity. Inversion approaches to estimate refractivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…To evaluate the inversion-based environment, refractivity for the forward models that resulted in lowest PL MSE are compared to the (refractivity) inverse solutions in Figure 9, where it should be noted that forward model cases with range dependent refractivity are averaged over range to improve legibility of the figure (e.g., COAMPS refractivity profile in Figure 9a). The most striking differences occur with respect to the mixed layer slope (e.g., Figures 9A, 9I or 9L); however, it has been shown that differences in the mixed layer slope do not affect propagation as significantly as other refractive parameters in the near surface (Lentini & Hackett, 2015;Matsko & Hackett, 2019;Pastore et al, 2021;Penton & Hackett, 2018), resulting in a relative insensitivity of the GA optimization to this parameter. Much more important is the duct height and the shape below the duct height (Cherrett, 2015;Pastore et al, 2021).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…To evaluate the inversion-based environment, refractivity for the forward models that resulted in lowest PL MSE are compared to the (refractivity) inverse solutions in Figure 9, where it should be noted that forward model cases with range dependent refractivity are averaged over range to improve legibility of the figure (e.g., COAMPS refractivity profile in Figure 9a). The most striking differences occur with respect to the mixed layer slope (e.g., Figures 9A, 9I or 9L); however, it has been shown that differences in the mixed layer slope do not affect propagation as significantly as other refractive parameters in the near surface (Lentini & Hackett, 2015;Matsko & Hackett, 2019;Pastore et al, 2021;Penton & Hackett, 2018), resulting in a relative insensitivity of the GA optimization to this parameter. Much more important is the duct height and the shape below the duct height (Cherrett, 2015;Pastore et al, 2021).…”
Section: Resultsmentioning
confidence: 98%
“…Although the lower average ΦMSE ${{\Phi}}_{\text{MSE}}$ for inversion PL confirms more accurate PL predictions, the better propagation predictions do not necessarily imply improved environmental predictions. The inversion approach may converge on an environment that only predicts the propagation accurately at the receiver heights and not necessarily everywhere, in other words, there can be nonunique solutions with a limited RF data set (Matsko & Hackett, 2019; Wang et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations